2016
DOI: 10.3747/co.23.3013
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Young Adult Cancer: Principles of Care

Abstract: Adolescents and young adults (ayas) with cancer in active treatment face a number of barriers to optimal care. In the present article, we focus on the 3 critical domains of care for ayas-medical, psychosocial, and research-and how changes to the system could overcome barriers. We summarize the current literature, outline recommended principles of care, raise awareness of barriers to optimal care, and suggest specific changes to the system to overcome those barriers in the Canadian context. Many of the recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…A meta-analysis found that medical and psychosocial issues for AYACs were common across studies. 17 Research issues were also included as a common barrier, which was defined as a lack of progress in improving AYACs' cure rates, but also the need for improving AYACs' transition to survivorship. 17 Current guidelines suggest that discussion of survivorship and transitioning to survivorship should be discussed at the very beginning of treatment for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found that medical and psychosocial issues for AYACs were common across studies. 17 Research issues were also included as a common barrier, which was defined as a lack of progress in improving AYACs' cure rates, but also the need for improving AYACs' transition to survivorship. 17 Current guidelines suggest that discussion of survivorship and transitioning to survivorship should be discussed at the very beginning of treatment for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Peer and family support are known to be important parts of the psychosocial support picture for AYAs [24].…”
Section: Discussionmentioning
confidence: 99%
“…Available research tends to evaluate technological‐based interventions with varied focuses, such as to improve psychosocial factors, communication, interactions, or neurological processing among CYA with chronic illnesses (Coyne et al., ; Karlson & Palermo, ; Majeed‐Ariss et al., ; Richter et al., ; Suzuki & Kato, ). Additionally, research on survivors of childhood cancers are also growing compared with the paucity of studies on CYA who are still affected by their cancer diagnoses (Barr et al, ; Ramphal et al., ). The difference in needs between survivors and diagnosed individuals seeks separate evaluations to prevent an overgeneralization of information (Foster & Fenlon, ; Richards, Corner, & Maher, ; Zebrack et al., ).…”
Section: Introductionmentioning
confidence: 99%